Volley Shoes Design Analysis with a Total Ergonomic Approach - Made Ida Mulyati; Nym Adiputra; Ketut Tirtayasa; I Putu Adiatmika (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Today the development of volleyball in the country is quite rapid, this is indicated by the increasing number of existing communities. Therefore, it is necessary to have a shoe design that can support the movement of volleyball in addition to being able to provide comfort and increase the performance of athletes. Unfortunately, despite the development of sports volleyball in soil water enough fast, however, development design of volleyball shoes did not experience significant development. This can be seen from the many complaints about the use of shoes on the market today. One of the problems that exist in the design of volleyball shoes, among others, is the complaint of feeling hot in the interior shoe because not enough presence ventilation on the upper part of shoes, and shoe soles are less flexible so that they are not able to support the jumping movement and there is no significant protection for the athlete's ankles when landing after jumping. Meanwhile, the shoes used by athletes do not fully provide a sense of comfort and cannot fully support volleyball movements. Some of the problems that arise are due to the lack of conducted analysis stages planning. Because that for getting design result shoe volleyball which truly good must through stages design which Correct. Besides, to provide comfort and satisfaction to the wearer in the analysis product should use approach ergonomics total (PET), through SHIP and appropriate technology (TTG).